Fungi from captive saltwater crocodile (Crocodylus porosus) eggs - Panes, Teresita S. (USM R & D Journal, 2011)
The study was conducted to isolate and identify the fungi in infertile eggs of captive saltwater crocodile (C. porosus) of Davao Crocodile Park at Maa, Davao City. The fungi that were identified were Aspergilus fumigatus, A. flavus, Penicillium sp. and an unidentified fungus. Their presence on eggs suggests that contimination may have come from the environment where the eggs were laid. This finding also suggest that since the eggs were infertile, the fungi may have contributed to their infertility.